2020
DOI: 10.1186/s12866-020-01899-0
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, virulence genes, and antimicrobial profiles of Escherichia coli O157 isolated from ruminants slaughtered in Al Ain, United Arab Emirates

Abstract: Background: Shiga toxin-producing Escherichia coli (STEC) is a major source of food-borne illness around the world. E. coli O157 has been widely reported as the most common STEC serogroup and has emerged as an important enteric pathogen. Cattle, in particular have been identified as a major E. coli O157:H7 reservoir of human infections; however, the prevalence of this organism in camels, sheep, and goats is less understood. The aim of this study was to evaluate the occurrence and concentration of E. coli serot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
0
8
2
Order By: Relevance
“…This incidence was slightly higher than 12.3% of pathogenic E. coli found in Kenya [20]. Conversely, the prevalence in our study was much higher than among 140 fecal samples collected from camels in the United Arab Emirates (4.3%) [21] and 3.8% among 600 fecal samples collected from camels in Nigeria [22].…”
Section: Resultscontrasting
confidence: 66%
See 1 more Smart Citation
“…This incidence was slightly higher than 12.3% of pathogenic E. coli found in Kenya [20]. Conversely, the prevalence in our study was much higher than among 140 fecal samples collected from camels in the United Arab Emirates (4.3%) [21] and 3.8% among 600 fecal samples collected from camels in Nigeria [22].…”
Section: Resultscontrasting
confidence: 66%
“…Bessalah et al [24] indicated that E. coli isolates were sensitive to ciprofloxacin, gentamicin, amikacin, chloramphenicol, and ceftiofur and resistant to ampicillin and tetracycline. Further, E. coli isolates were 100% susceptible to ciprofloxacin, norfloxacin, cefotaxime, chloramphenicol, and polymyxin B [21]. yaiO is a housekeeping gene of E. coli, and its detection confirms that isolates are E. coli strains.…”
Section: Resultsmentioning
confidence: 89%
“…Similar detection rates of E. coli from she-camels were observed by Al Humam [ 41 ], who detected isolates in 26% of cases. Contrariwise, these findings were lower when compared with those formerly reported by El-Hewairy et al [ 42 ] and Al-Ajmi et al [ 43 ]. Conversely, our findings are higher than those reported by Shahein et al [ 7 ], where E. coli was isolated from 17.1% of the examined fecal samples collected from diarrheic camels.…”
Section: Discussioncontrasting
confidence: 76%
“…Conversely, our findings are higher than those reported by Shahein et al [ 7 ], where E. coli was isolated from 17.1% of the examined fecal samples collected from diarrheic camels. Several studies were undertaken to assess the prevalence of E. coli in fecal samples collected from diarrheic camels in Qatar [ 44 ], United Arab Emirates [ 43 ], Kenya [ 45 ], and Nigeria at 3.8% [ 46 ]. However, El-Sayed et al [ 18 ] failed to detect any STEC from camel feces.…”
Section: Discussionmentioning
confidence: 99%
“…Enterohemorrhagic E. coli O157 belongs to the larger category of Shiga toxin-producing E. coli (STEC), which can produce Shiga toxin type 1 (Stx1), Shiga toxin type 2 (Stx2), or both, along with other variants [13][14][15].…”
Section: Introductionmentioning
confidence: 99%